2017
DOI: 10.1136/oemed-2017-104651
|View full text |Cite
|
Sign up to set email alerts
|

Half-lives of PFOS, PFHxS and PFOA after end of exposure to contaminated drinking water

Abstract: BackgroundMunicipal drinking water contaminated with perfluorinated alkyl acids had been distributed to one-third of households in Ronneby, Sweden. The source was firefighting foam used in a nearby airfield since the mid-1980s. Clean water was provided from 16 December 2013.ObjectiveTo determine the rates of decline in serum perfluorohexane sulfonate (PFHxS), perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA), and their corresponding half-lives.MethodsUp to seven blood samples were collected betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
370
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 582 publications
(382 citation statements)
references
References 20 publications
9
370
3
Order By: Relevance
“…Data from 26 retired fluorochemical production workers (24 men, 2 women) indicate the average serum half-life of PFHxS is 7.3 years (8.5 years geometric mean) 35 -with a noted, although not statistically significant, higher average in women than in men (12.8 versus 8.2 years). A recent study of 106 participants of a previously exposed population found a shorter half-life of 5.3 years 36 . Similar to PFBS, these studies show a pattern of elimination rates highest in rats, lower in monkeys, and the lowest in humans.…”
Section: Pfhxsmentioning
confidence: 96%
“…Data from 26 retired fluorochemical production workers (24 men, 2 women) indicate the average serum half-life of PFHxS is 7.3 years (8.5 years geometric mean) 35 -with a noted, although not statistically significant, higher average in women than in men (12.8 versus 8.2 years). A recent study of 106 participants of a previously exposed population found a shorter half-life of 5.3 years 36 . Similar to PFBS, these studies show a pattern of elimination rates highest in rats, lower in monkeys, and the lowest in humans.…”
Section: Pfhxsmentioning
confidence: 96%
“…Several PFASs are bioaccumulating, 1 and they are extremely persistent in the environment. 1 The half-lives of PFAS compounds have been estimated to be in the range of 3-5 years, 2 and some of them have been found to be transferable through the placenta. 3 Therefore, human exposure, which is shown worldwide, will continue for a long time, despite any regulations or phasing-out.…”
Section: Introductionmentioning
confidence: 99%
“…The half-lives of individual PFAS in humans depend both on the carbon chain length and functional groups. For PFOA, PFOS and PFHxS, half-lives in humans range between 2.7 to 5.3 years [49,50]. Half-lives for shorter chain compounds, such as PFBS, are approximately one month [51].…”
Section: Is Electrophilic or Can Be Metabolically Activatedmentioning
confidence: 99%